Drivers behaviour on expressways: headway and speed relationships. (May 2019) - Puan, O. C.; Mohamed, A.; Idham, M. K.; Ismail, C. R.; Hainin, M. R.; Ahmad, M. S. A.; Mokhtar, A.
Abstract: This paper describes result of a study on driver's car following behaviour on Malaysian high-speed highways. Drivers' car following behaviour can considered as one of the main factors that causes road accidents to occur such as rear end collision between vehicles on highways. The aim of the study was to examine the safe following distance adopted by drivers on expressways at various operating speeds. An automatic traffic recording device attached with pneumatic tubes was used to record traffic movement at three selected expressway segments in Malaysia for six consecutive days. More than one hundred thirty three thousand (133, 000) headway and speed data were involved in the analysis. The distance headway and associated speed collected were classified into five vehicle following categories by vehicle type, i.e. all vehicles, car following car, car following heavy goods vehicle (HGV), HGV following HGV, and HGV following car. Linear regression models were used to develop relationship between distance headway and speed. The relationships developed can be regarded as reliable since the R 2 -values for each of the relationships is in the range of 0.80 to 0.99 and can be used to estimate a safe following distance perceived by a driver at a given speed. The driver's average response time on an expressway is 3.06 sec which is 1.9 sec longer than those who are driving on a two-lane single-carriageway road. Such a variation in response time indicates that the level of aggressiveness of drivers on a two-lane single-carriageway road are higher than the drivers on an expressway.